Private Sector Development in State-Dominated Economies - Husain, Aasim (IMF Working Papers; Working Paper ;, 1992)
The development of a competitive private sector is widely viewed as a central element in the economic transformation of central and eastern Europe. Despite significant reforms in these economies, however, state enterprises continue to produce a substantial share of output. This paper considers how the profitability of private firms is affected by the size of the state-owned sector. Closures that result in a decrease in the number of state-owned firms reduce total industrial output in the short run, but encourage the entry of private firms into the industry in the longer run and lead to an increase in total output. Policies that result in a depreciation of the real exchange rate or an improvement in the efficiency of credit markets will tend to increase output in the short run, but their effect may be attenuated in the long run.